Technical rationality as an instrument of power: an essay on the project prioritization model in the Guatemalan state (Revista revoluciones, 2026)
Guatemala has a regulatory framework and technical guidelines for the formulation and evaluation of projects, but not for the identification and prioritization of projects, resulting in a critical gap between institutional design and practical political implementation. The objective of this work was to analyze the process of prioritizing public investment projects in Guatemala through a documentary review of regulations and investment methodology documentation. It was found that the technique does not operate as a mechanism of public rationality, turning the project planning process solely into a political tool, lacking scientific rigor, and being displaced by particular interests. When autonomous decline is found in the technique, its strategic value is lost, and it becomes part of the bureaucratic pretext that conceals clientelism and lack of transparency in resource management. Strong discretion is noted as the main driver that deepens territorial inequalities, since project prioritization does not respond to criteria of social reality or equity, but rather to political profitability, favoring urban areas over rural ones, causing structural exclusion of the most vulnerable communities, where public investment, instead of reducing gaps, widens them, eroding citizen trust. It is highlighted that to reverse this phenomenon, a transformation toward a process-based management model is proposed, one that professionalizes public service, for the construction of democratic governance where technique regains its redistributive and social justice function.
Keywords: state; investment; projects; rationality